Digital interventions for weight control to prevent obesity in adolescents: a systematic review - De Luca, Vincenzo; Virgolesi, Michele; Vetrani, Claudia; Aprano, Sara; Cantelli, Federica; Di Martino, Annamaria; Mercurio, Lorenzo; Iaccarino, Guido; Isgrò, Francesco; Arpaia, Pasquale; Colao, Annamaria; Illario, Maddalena (Frontiers in Public Health, 2025)
BackgroundObesity is a common, serious, and costly chronic disease of adults and children that poses serious long-term health risks. Recent global estimates from the World Health Organization (WHO) show that the number of adolescents living with overweight or obesity is now increasing in low- and middle-income countries, particularly in urban settings. Health interventions using information technology (IT), especially diet and activity tracking, can lead to significant reductions in weight status.ObjectiveThis systematic review aimed to map IT-supported interventions designed to prevent obesity in adolescents, promoting healthy nutrition and physical activity. Methods: The Preferred Reporting Items for Systematic Reviews and Meta-Analyses checklist was used. A search of the electronic databases Medical Literature Analysis and Retrieval System Online (MEDLINE) and Excerpta Medica Database (EMBASE) was conducted using search terms in various combinations appropriate to the research objective. The Effective Public Health Practice Project (EPHPP) quality assessment tool was used to assess quality.ResultsA total of 21 English language studies were eligible for inclusion. The systematic review synthesized information on weight control IT-supported intervention trials to prevent obesity, their domains of intervention, implementation setting, digital tool adopted, and the outcomes assessed.ConclusionThe interventions included in the present study mainly concern nutritional aspects and physical activity, but motivational and psychological support also play a fundamental role in their success.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42024412913, identifier [CRD42024412913].